Simultaneous Nitrification–Denitrification of Wastewater: Effect of Zeolite as a Support in Sequential Batch Reactor with Step-Feed Strategy - Huilinir-Curio, C; Montalvo-Martinez, S (Center for Environmental and Energy Research and Studies, 2016)
One of the technologies used for wastewater nitrogen removal consists in simultaneous nitrification–denitrification. The low microbial growth rate and the low availability of organic material for the denitrification stage make it necessary to study new operational conditions and the use of microbial supports. The aim of this study was to evaluate the operational behavior of a simultaneous nitrification–denitrification process in a sequential batch reactor utilizing zeolite as a biomass support and step-feed strategy. Two reactors of 2 L were used, one with zeolite and another without zeolite, both operated at constant temperature (31 °C), varying nitrogen loading rate (NLR) from 0.041 to 0.113 kg total Kjeldahl nitrogen (TKN/m3/day). After 209 days, removals higher than 86 and 96 % in nitrogen compounds and organic matter were obtained, respectively. There was not accumulation of nitrate and nitrite in any case; this means that there was a simultaneous nitrification–denitrification in the reactors. The incorporation of zeolite in the system held higher concentration of biomass in the reactor; this led to reduce start-up to 21 days and to improve 11.31 % removal kinetic. The use of a step-feed strategy prevents events of inhibition by substrate, even duplicating tolerance to higher NLR for the same operation time. © 2016, Islamic Azad University (IAU).